The history of the Arthaśāstra: sovereignty and sacred law in ancient India - McClish, Mark (Ideas in context, 2019)
The Arthaśāstra is the foundational text of Indic political thought and ancient India's most important treatise on statecraft and governance. It is traditionally believed that politics in ancient India was ruled by religion; that kings strove to fulfil their sacred duty; and that sovereignty was circumscribed by the sacred law of dharma. Mark McClish's systematic and thorough evaluation of the Arthaśāstra's early history shows that these ideas only came to prominence in the statecraft tradition late in the classical period. With a thorough chronological exploration, he demonstrates that the text originally espoused a political philosophy characterized by empiricism and pragmatism, ignoring the mandate of dharma altogether. The political theology of dharma was incorporated when the text was redacted in the late classical period, which obscured the existence of an independent political tradition in ancient India altogether and reinforced the erroneous notion that ancient India was ruled by religion, not politics.